Comparison of some biokinematic variables for the skill of serving and indicators of physical composition among the players of the Iraqi universities teams in table tennis (Journal of the College of Basic Education, 2022)
The study aimed to identify some bio-kinematic variables of the skill of serving and indicators of physical structure, as well as to identify the differences in some bio-kinematic variables of the skill of transmission and indicators of physical structure of the players of the Iraqi universities teams for table tennis. ) Universities (Universities of Baghdad, Al-Mustansiriya, Technology, Babel, Al-Hadba, Al-Qadisiyah, and Kirkuk) participating in the Iraqi Universities Table Tennis Championship. player for each group. After processing the results statistically